PENGARUH HEDONIC SHOPPING, FASHION INVOLVEMENT, STORE ENVIRONMENT DAN PRICE DISCOUNT TERHADAP IMPULSE BUYING PADA STORE THREE SECOND DI LIPPO PLAZA MALL JEMBER - Bambang Irawan; Gusti Ayu Wulandari; Nila Anindya Anggraini; N. Ari Subagio; Ketut Indraningrat (VALUE: Journal of Business Studies, 2022)
This study is purposed to examine the impact of hedonic shopping, fashion involvement, store environment and price discounts on impulse buying at the Three Second Lippo Plaza Mall Jember store. This study uses a sample of consumers who shop impulsively at the Three Second Lippo Plaza Mall Jember store, the side method used isnon-probability sampling with respondents as many as 96 consumers. The analytical technique used is multiple linear regression analysis. The results showed that hedonic shopping, fashion involvement, store environment and price discounts on impulse buying at the Three Second Lippo Plaza Mall Jember store in a positive direction. The business actors still maintain hedonic shopping, fashion involvement, store environment and price discounts in impulse buying.